ANALISIS KESULITAN DALAM MENYELESAIKAN SOAL CERITA BAHASA INDONESIA SISWA KELAS V DI UPT SDN INPRES 163 BONTOPANNO KABUPATEN TAKALAR - Safitri, Nur Indah; Andi Paida; Wahyu Ningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students' difficulties in solving word problems in the Indonesian language subject for fifth-grade students at UPT SDN Inpres 163 Bontopanno, Takalar Regency. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of 20 fifth-grade students. Data collection techniques included tests, observations, interviews, and documentation. The data analysis techniques involved data reduction, data display, and conclusion drawing. The results of the study indicate that students' ability to solve word problems is still not optimal. Students experience several difficulties, including difficulties in understanding the content of the text, identifying the main idea, determining the message of the text, and expressing answers clearly and systematically. The factors causing these difficulties consist of internal and external factors. Internal factors include low reading interest, limited vocabulary mastery, and lack of self-confidence. Meanwhile, external factors include less varied teaching methods and the suboptimal use of learning media. Based on these findings, improvements in the learning process are needed through the use of more innovative teaching methods, enhancement of reading literacy activities, and continuous practice to improve students' ability in solving word problems effectively.